Diabetes and glucose disturbances in patients with psychosis in Sweden. Issue 1 (9th October 2015) - Olsson, Eric; Westman, Jeanette; Sudic Hukic, Dzana; Eriksson, Sven V; Edman, Gunnar; Bodén, Robert; Jedenius, Erik; Reutfors, Johan; Berntsson, Anders; Hilding, Agneta; Schalling, Martin; Östenson, Claes-Göran; et al.
Abstract : Objective: The objectives of this study were to (1) analyze the prevalence of diabetes, prediabetes, and antidiabetic medication in patients with psychosis compared with control subjects and (2) determine what factors in patients with psychosis were associated with antidiabetic medication. Method: We studied 977 patients with psychosis recruited from outpatient clinics in Stockholm County, Sweden, and they were compared with 3908 non-psychotic control subjects for fasting plasma glucose levels; prevalence of diabetes, prediabetes, antidiabetic treatment, and tobacco use; and blood pressure, weight, height, and waist circumference. Group differences were evaluated with analysis of variance and χ 2 test, and factors associated with antidiabetic treatment were evaluated with logistic regression. Results: Diabetes was observed in 94 (10%) patients with psychosis, 2.7 times the prevalence observed in control subjects. Among patients with psychosis, 87 (10%) had prediabetes (fasting glucose, 6.1–6.9 mmol/L) compared with 149 (3.8%) control subjects. Most patients with psychosis (77%) who had prediabetes fulfilled criteria for metabolic syndrome. In patients with psychosis, both lipid-lowering medication and fasting glucose were significantly associated with antidiabetic treatment. There was no significant relation between antidiabetic treatment and lifestyle factors such as smoking or degree of psychiatric illness. Conclusions: The high prevalence of impaired fasting glucose and metabolic syndrome in patients with psychosis warrants further clinical research in preventing or delaying the onset of diabetes in these patients by pharmacotherapy and/or lifestyle intervention.